Solve the equation
- 1
- m - 7 = 5
3

Answers

Answer 1
Answer:

1/3m-7=5

One solution was found :

m = 36
Rearrange:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

1/3*m-7-(5)=0

Step by step solution :

Step 1 :

1
Simplify —
3
Equation at the end of step 1 :

1
((— • m) - 7) - 5 = 0
3
Step 2 :

Rewriting the whole as an Equivalent Fraction :

2.1 Subtracting a whole from a fraction

Rewrite the whole as a fraction using 3 as the denominator :

7 7 • 3
7 = — = —————
1 3
Equivalent fraction : The fraction thus generated looks different but has the same value as the whole

Common denominator : The equivalent fraction and the other fraction involved in the calculation share the same denominator

Adding fractions that have a common denominator :

2.2 Adding up the two equivalent fractions
Add the two equivalent fractions which now have a common denominator

Combine the numerators together, put the sum or difference over the common denominator then reduce to lowest terms if possible:

m - (7 • 3) m - 21
——————————— = ——————
3 3
Equation at the end of step 2 :

(m - 21)
———————— - 5 = 0
3
Step 3 :

Rewriting the whole as an Equivalent Fraction :

3.1 Subtracting a whole from a fraction

Rewrite the whole as a fraction using 3 as the denominator :

5 5 • 3
5 = — = —————
1 3
Adding fractions that have a common denominator :

3.2 Adding up the two equivalent fractions

(m-21) - (5 • 3) m - 36
———————————————— = ——————
3 3
Equation at the end of step 3 :

m - 36
—————— = 0
3
Step 4 :

When a fraction equals zero :

4.1 When a fraction equals zero ...
Where a fraction equals zero, its numerator, the part which is above the fraction line, must equal zero.

Now,to get rid of the denominator, Tiger multiplys both sides of the equation by the denominator.

Here's how:

m-36
———— • 3 = 0 • 3
3
Now, on the left hand side, the 3 cancels out the denominator, while, on the right hand side, zero times anything is still zero.

The equation now takes the shape :
m-36 = 0

Solving a Single Variable Equation :

4.2 Solve : m-36 = 0

Add 36 to both sides of the equation :
m = 36

One solution was found :

m = 36

I happen this help

Related Questions

1 added by 1 is A. 2B. 3C. 5D. 11 Explain your answer​
Find the mD5535В
Which scatter plot could have a trend line whose equation is y = x + 15?​
Need help will mark Brainliest no explanation needed
Inflation and Interest Rates: Tutorial22 of 25Save & ExitQuestionConsider a simple economy where the basket of goods used to calculate the CPI contains two items shampoo and soap.The basket consists of 1 bottle of shampoo and 2 bars of soap. The prices are shown in the table.Year Price of a Bottle of Shampoo Price of a Bar of SoapYear36 50$1.25Year$5.00$1.30Type the correct answer in the box. Round your answers to two decimal places, if necessary.The CPI for year 2 isSubmit

SIMPLE GRAPHING EQUATION (CORRECT ANSWER = BRAINLIEST, THANKS, 5 STAR, AND A COMMENT + THE POINTSFind the value of “b” so that the slope of the line passing through the points A(5, –8) and B(–1, b) is –2.

Answers

Answer:

b=4

Step-by-step explanation:

For this question we need to know the formula of slope that is m which is

m=(y_2-y_1)/(x_2-x_1)

where (x_1,y_1) , (x_2,y_2) are the points (5,-8),(-1,b) respectively

and hence we have the value of m= -2 which is the slope we simply plug in all the values.

m=(y_2-y_1)/(x_2-x_1)\n\n-2=(b-(-8))/(-1-5) \n\n-2=(b+8)/(-6) \n\n12=b+8\n12-8=b\n4=b

So the value of b=4

Answer:

b is 4

Step-by-step explanation:

Several steps are required to find this answer. You need to use the information you are given as well as the formula y=mx+b. You are given the slope and one of the coordinates. Plug the information into the formula to find b, which is the constant.

The point given is (5,-8)

The slope given is -2

Plug the x and y into y=mx+b

-8=-2(5)+b

-8=-10+b

-8+10=b

b=2

Now that you have the full equation, y=-2x+2 , you can plug in the x-coordinate of the other coordinate to find the missing y-value.

y=-2(-1)+2

y=2+2

y=4

Therefore, the b you are solving for is 4.

Can someone help me out on this ASAP??

Answers

Answer:

sin X = cos Y

Step-by-step explanation:

sin X = opp / hyp = 3/5

Cos y = adj / hyp = 3/5

sin X = cos Y

Determine the value of x for which a || b if m∠1 = 60 - 2x and m∠5 = 70 - 4x.50
5
4
10

Answers

x is equal  to 10 cuz u would sub 70-60


Two​ fire-lookout stations are 190 miles ​apart, with station A directly south of station B. Both stations spot a fire. The bearing of the fire from station A is Upper N 55 degrees Upper E and the bearing of the fire from station B is Upper S 60 degrees E. How​ far, to the nearest tenth of a​ mile, is the fire from each lookout​ station?

Answers

Step-by-step explanation:

Let's say the position of the fire is point C.

Bearings are measured from the north-south line.  So ∠BAC = 55°, and ∠ABC = 60°.

Since angles of a triangle add up to 180°, ∠ACB = 65°.

Using law of sine:

190 / sin 65° = a / sin 60° = b / sin 55°

Solving:

a = 181.6

b = 171.7

Station A is 181.6 miles from the fire and station B is 171.7 miles from the fire.

Consider the series 4+8+16+32+...
What is the common ratio?

Answers

The common ratio is 24 x 2 = 88 x 2 = 1616 x 2 =32
Can I get Brainliest?
Thanks

Equations
Solve T = C(9+ AB) for B

Answers

Answer:

Simplifying

T = C(9 + AB) * forB

Reorder the terms for easier multiplication:

T = C * forB(9 + AB)

Multiply C * forB

T = forBC(9 + AB)

T = (9 * forBC + AB * forBC)

Reorder the terms:

T = (forAB2C + 9forBC)

T = (forAB2C + 9forBC)

Solving

T = forAB2C + 9forBC

Solving for variable 'T'.

Move all terms containing T to the left, all other terms to the right.

Simplifying

T = forAB2C + 9forBC

Step-by-step explanation:

Simplifying

T = C(9 + AB) * forB

Reorder the terms for easier multiplication:

T = C * forB(9 + AB)

Multiply C * forB

T = forBC(9 + AB)

T = (9 * forBC + AB * forBC)

Reorder the terms: